ECG for Detection of Left Ventricular Hypertrophy in patients with Chronic Kidney Disease - Huma Hussain, Muniza Saeed, Hifza Noor Lodhi, Shagufta Khaliq, Afsheen Zakir, Naila Masood Riaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Left ventricular hypertrophy is the most common cardiac event associated with chronic kidney disease. Aim: To detect LVH by electrocardiography in patients with CKD. Study design: Observational study. Methodology: It was an observational study with total of 62 CKD patients enrolled through convenience sampling. Their blood 3ml was drawn aseptically for estimation of serum creatinine. All enrolled subjects underwent electrocardiographic examination. Patients with low GFR (<60ml/min/1.73m2) and high serum creatinine concentration (>1.5mg/dl) were included. Data was evaluated by using SPSS vr 24. The results were presented as counts, means and standard deviation as appropriate. Results: Left ventricular hypertrophy was present in 50% of enrolled patients as depicted by ECG recording. The calculated sensitivity and specificity of ECG for LVH were 75% and 100% respectively. Almost 38.7% patients were 56-65 years of age. There were 33.9% patients in the age of 35-45 years and 27.4% was in the age of 46-55 years. The median (IQR) age was 54.50 (41.75-60) years. In our study population, median (IQR) of height was 152cm (150-156). The mean weight was 65.85 kg with standard deviation of 8.42 kg i.e., 65.85 ±8.42kg. Mean body mass index was 27.85. Practical Implication: Current project helped health providers to diagnose cardiac event at an early stage among patients of kidney failure on ECG findings thus the adverse outcomes could be prevented or delayed. Conclusion: ECG abnormalities are common in hospitalized CKD patients in local population. All hospitalized CKD patients should undergo ECG to screen for cardiovascular disease. It was thus concluded that ECG can be used as a sensitive diagnostic tool in combination with different ECG indices to detect LVH. Key words: Electrocardiography, Chronic Kidney Disease, Left Ventricular Hypertrophy and Sokolow-Lyon Voltage Index.